PENGEMBANGAN MEDIA MOTION GRAPHIC MENGGUNAKAN POWTOON PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Jamila, Raudatul; Nelly Astimar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the lack of variety in learning media, as well as the lack of use of technology in learning media innovation. This research aims to develop motion graphic learning media using Powtoon in science and science learning in class V elementary schools that is valid, practical and effective. This type of research is development research (R&D) using the ADDIE model which consists of analysis, design, development, implementation and evaluation. Data collection uses validation sheets, response questionnaires, and evaluation sheets. The test subjects in this research were class V students at SDN 12 Padang Besi and SDN 21 Bandar Buat. The results of this research showed that learning media had an average validation percentage level of 94.99% in the very valid category. The results of the practicality of teacher responses at SDN 12 Padang Besi and SDN 21 Bandar Buat obtained an overall average of 94.63% in the very practical category. Practicality Results of Student Responses at SDN 12 Padang Besi obtained a percentage of 91.25% and SDN 21 Bandar Buat obtained a percentage of 93.48% with the second category being very practical. The results of the effectiveness of learning media in class V at SDN 12 Padang Besi obtained a percentage increase in student learning outcomes of 90% with 80% completeness at the first meeting and 95% with 85% completeness at the second meeting. Meanwhile, the results of the effectiveness of learning media in class V at SDN 21 Bandar for the first meeting obtained a percentage of 93.75% with 87.5% completeness and at the second meeting it was 87.5% with 81.25% completeness. Based on these results, it can be concluded that this media has proven to be valid, practical and effective for use in the learning process.